2022
DOI: 10.1108/bjm-11-2021-0449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transformational leadership and work engagement on managers’ creative performance

Abstract: PurposeThe purpose of the study is to investigate the effect of transformational leadership on creative performance in managers and the mediation effect of work engagement. The study also explores whether manager autonomy is a moderator of the model.Design/methodology/approachThe authors captured information about transformational leadership, work engagement, creative performance and autonomy, using an experimental design and surveys among a sample of managers. They modeled the first-stage moderated mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…For instance, a company needs to generate managers’ work engagement to perform better. Engaged managers are more creative in promoting an innovative climate for other employees and have better creative performance ( Juyumaya and Torres, 2023 ). Firms need to address these issues via diverse strategies, such as talent management, training and development, and incentive programs to handle manager work engagement in the workplace ( Asija and Ringov, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a company needs to generate managers’ work engagement to perform better. Engaged managers are more creative in promoting an innovative climate for other employees and have better creative performance ( Juyumaya and Torres, 2023 ). Firms need to address these issues via diverse strategies, such as talent management, training and development, and incentive programs to handle manager work engagement in the workplace ( Asija and Ringov, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…. Scholars such asLu et al (2022),Aboramadan et al (2022),Jahangir et al (2023),Zaman and Ansari (2023), andJuyumaya and Torres (2023) have confirmed the positive and significant connection between work engagement and innovative behaviour, business growth, and subjective business success in various contexts. Furthermore, empirical evidence fromGorgievski et al (2013) reveals a significant positive effect of work engagement on job performance based on a sample of 180 individuals.…”
mentioning
confidence: 90%
“…Transformational leaders tend to change individuals and organisations considering their values, ethics, standards as well as long term goals. Transformational leaders are characterised by their ability to create a compelling vision, stimulate intellectual growth, encourage creativity, and promote a sense of shared purpose and commitment among their followers (Bass & Riggio, 2006;Juyumaya & Torres, 2023). According to Bass and Riggio (2006) the key components of transformational leadership include: i.…”
Section: Overview Of Transformational Leadershipmentioning
confidence: 99%